Adsorption of Heavy Metals in Contaminated Water Using Zeolite Derived from Agro-Wastes and Clays: A Review - Ismael Kithinji Kinoti; Joanne Ogunah; Cyprian Muturia M’Thiruaine; Joseph Mwiti Marangu (Journal of Chemistry)
Due to climate change and anthropogenic activities such as agriculture, mining, and urbanization, water contamination has become a very real modern problem. Modern solutions such as activated carbon, reverse osmosis, and ultrafiltration, among others, have been employed in the decontamination of water. These methods are, however, expensive to set up and maintain and therefore have proved a challenge to implement in developing countries. Zeolite materials exhibit excellent structural properties, such as high ion exchange capacity, porosity, and relative surface area, which make them attractive to water decontamination processes. However, conventional zeolites are expensive, and recent research has focused on utilizing low-cost materials such as agro-wastes and clays as raw materials for the synthesis of zeolites. This review aims to discuss the role of low-cost zeolites in their removal of heavy metals and the feasibility of agro-wastes and natural clays in the synthesis of zeolites. Recent research studies based on the synthesis of zeolites from clays and agro-wastes and their application in heavy metal removal have been reviewed and discussed. Agro-wastes such as rice husk ash and sugarcane bagasse ash and layered silicate clays such as kaolinite and smectites are particularly of interest to zeolite synthesis due to their high silica to alumina ratio. Zeolites synthesized through various methods such as hydrothermal, molten salt, and microwave irradiation synthesis have been discussed with their effect on the adsorption of various heavy metals.